2015
DOI: 10.1159/000441711
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Case of Multiple Tendinous Xanthomas Involving the Extremities and the Ears

Abstract: Tendinous and subcutaneous xanthomas are nodular deposits of lipid-filled macrophages, which commonly form on the Achilles tendon, hands, feet, elbows, and knees. These nodules are frequently associated with familial hyperlipidemia, a group of diseases involving impaired cholesterol metabolism, and the accelerated development of atherosclerotic plaques. Since xanthomas may precede the diagnosis of hyperlipidemia, early identification can lead to preventative treatment that reduces the risk and morbidity of car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Studies have shown that the most frequent site for xanthomas in these patients is the Achilles tendon . Other sites can include the extensor tendons of the hands and feet, as the extensor tendon areas are subject to mechanical stress …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies have shown that the most frequent site for xanthomas in these patients is the Achilles tendon . Other sites can include the extensor tendons of the hands and feet, as the extensor tendon areas are subject to mechanical stress …”
Section: Discussionmentioning
confidence: 99%
“…Other conditions that could be considered in the differential diagnosis of xanthomas occurring at ankles and knees are as follows: giant cell tumor of tendon sheath, diffuse villonodular synovitis, lipoma, neurofibroma and rarely sarcomas. Appropriate clinical setting and cytology would lead to the right diagnosis in such situations …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations